2008
DOI: 10.1007/s11199-008-9483-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Dimensionality and Other Psychometric Properties of a Greek Translation of the Sex-role Egalitarianism Scale (Form B)

Abstract: The main purpose of this study was to investigate the dimensionality of a Greek-language version of the Sex Role Egalitarianism Scale-Form B (SRES-B) via confirmatory factor analysis. Using two different samples (undergraduates and community sample from Greece) data from 667 individuals were collected. Three models were specified: the five-factor model (marital, parental, socialinterpersonal-heterosexual, employment, and educational roles); the two-factor model (Intimate and Formal); and the single-factor mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Although this is a particular American context, and American culture likely influences both egalitarianism and the boot camp experience, this research may be relevant to women's experiences in other countries, as women are a growing presence in traditionally male-dominated military, educational, and business institutions worldwide. Our measure of gender-role attitudes, the SRES (King and King 1983;King and King 1993), has been translated into a number of languages and normed on different populations worldwide, making it particularly relevant to international researchers (Katenbrink 2006;Pavlou et al 2008;Ui and Matsui 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although this is a particular American context, and American culture likely influences both egalitarianism and the boot camp experience, this research may be relevant to women's experiences in other countries, as women are a growing presence in traditionally male-dominated military, educational, and business institutions worldwide. Our measure of gender-role attitudes, the SRES (King and King 1983;King and King 1993), has been translated into a number of languages and normed on different populations worldwide, making it particularly relevant to international researchers (Katenbrink 2006;Pavlou et al 2008;Ui and Matsui 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of research on young individuals in Turkey indicates that males tend to adopt more non-egalitarian roles (Çetinkaya Kodan, 2013;Ergin et al, 2019;Palas Karaca & Çubukçu Aksu, 2020;Uçar et al, 2017). This is supported by various studies that have consistently shown that young women tend to exhibit more egalitarian attitudes than young men (Askari et al, 2010;Dotti Sani & Quaranta , 2017;Freund et al, 2013;Marcos & Bahr, 2001;Pavlou et al, 2008). For instance, Dotti Sani and Quaranta (2017) found that even in adolescence, young women show more egalitarian attitudes than young men and avoid conforming to traditional gender roles.…”
Section: Conclusion and Discussionmentioning
confidence: 74%